2008
DOI: 10.1016/j.clinbiomech.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of loading rate and degeneration on neutral region motion in human cadaveric lumbar motion segments

Abstract: Background-The quasistatic neutral zone is a surrogate for neutral region stiffness of spinal motion segments. No similar measure of dynamic stiffness has been validated. Because parameters related to stiffness are likely to be affected by loading rate and disc degeneration, we examined the effect of those factors on motion parameters derived from continuous motion data. Methods-Fifteenhuman lumbar motion segments were tested with continuous flexion-extension pure moments at 0.5, 3.0 and 6.0 degrees/second. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…The degenerative degree is graded radiographically following the scale introduced by Wilke et al [76] Eur Spine J From early studies, consensus about an increase of the size of the neutral zone in all the three main directions for degenerated discs seemed to emerge [45,51]. More recently, other studies either confirmed these trends [23] or showed no-or hardly any-change in its size between healthy and degenerated motion segments [63]. In the aforementioned retrospective paper about a wide number of degenerated specimens [37], an increase in the neutral zone was found only in axial rotation, and was not limited to mild degeneration, but progressed with the presence of severe degenerative changes (Fig.…”
Section: Neutral Zonementioning
confidence: 99%
“…The degenerative degree is graded radiographically following the scale introduced by Wilke et al [76] Eur Spine J From early studies, consensus about an increase of the size of the neutral zone in all the three main directions for degenerated discs seemed to emerge [45,51]. More recently, other studies either confirmed these trends [23] or showed no-or hardly any-change in its size between healthy and degenerated motion segments [63]. In the aforementioned retrospective paper about a wide number of degenerated specimens [37], an increase in the neutral zone was found only in axial rotation, and was not limited to mild degeneration, but progressed with the presence of severe degenerative changes (Fig.…”
Section: Neutral Zonementioning
confidence: 99%
“…The effect of deformation rate on the mechanical properties of soft biological tissues has been investigated, in particular for ligaments [1][2][3][4][5][6][7], tendons [4,[7][8][9], spines [10][11][12][13], bones [14][15][16][17], liver [18], heart valves [19,20] and myocardium [21,22]. Most biological tissues stiffen with increasing deformation rate [4,7,9,[11][12][13]17].…”
Section: Introductionmentioning
confidence: 99%
“…Similar increases in stiffness in the neutral zone of human FSU specimens were reported by Gay et al due to an increase in test frequency from 0.5-6.0°/s in pure moment testing in the sagittal plane. 77 The temperature of specimens also has effects on the measured stiffness. Bass et al reported that the stiffness of the ALL was 38% greater at 21.1°C compared to 37.8°C.…”
Section: 75mentioning
confidence: 99%